Enhanced Magnetorheological Performance of Carbonyl Iron Suspension Added With Barium Ferrite Nanoparticle - Jang, Hyo Seon; Lu, Qi; Choi, Hyoung Jin (Frontiers in Materials, 2021)
Hard-magnetic barium ferrite (BF) nanoparticles with a hexagonal plate-like structure were used as an additive to a carbonyl iron (CI) microparticle-based magnetorheological (MR) fluid. The morphology of the pristine CI and CI/BF mixture particles was examined by scanning electron microscopy. The saturation magnetization and coercivity values of each particle were measured in the powder state by vibrating sample magnetometry. The MR characteristics of the CI/BF MR fluid measured using a rotation rheometer under a range of magnetic field strengths were compared with those of the CI-based MR fluid. The flow behavior of both MR fluids was fitted well to a Herschel-Bulkley model, and their stress relaxation phenomenon was examined using the Schwarzl equation. The MR fluid with the BF additive showed higher dynamic and elastic yield stresses than the MR fluid without the BF additive as the magnetic field strength increased. Furthermore, the BF nanoparticles embedded in the space between the CI microparticles improved the dispersion stability and the MR performance of the MR fluid.